Enhancer of zeste homolog 2 is a negative prognostic biomarker and correlated with immune infiltrates in meningioma - Zeng, Jing; Sun, Lu; Huang, Jiaming; Yang, Xia; Hu, Wanming (Frontiers in Neuroscience, 2022)
Background: Enhancer of zeste homolog 2 (EZH2), an important epigenetic regulator, that mainly regulates histone H3 lysine 27 trimethylation (H3K27me3) through histone methyltransferase, and participates in promoting the development of tumors. At present, the loss of H3K27me3 expression in meningioma is a poor prognostic factor, but the research of EZH2 in meningioma is rare. Therefore, we aim to explore the expression of EZH2 in the meningioma and its correlation with the prognosis and immune microenvironment and lay the foundation for the subsequently potential targeted therapy and immunotherapy for meningioma. Methods: Tissue microarray immunohistochemistry staining was performed on 276 meningioma samples from Sun Yat-sen University Cancer Center. Expression levels of EZH2, H3K27me3, Ki67, PD-1, PD-L1, CD4, CD8, CD20, FOXP3, CD68, and CD163 were evaluated. Cox regression analyses were performed, and the Kaplan-Meier method was used to construct survival curves. In addition, we use biological information methods to analyze the mRNA expression of EZH2 and its relationship with the prognosis and immune microenvironment in the GEO database. Result: EZH2 expression is concentrated in WHO grades 2 and 3 meningiomas (8.3%+ & 33.3%+). We found that EZH2 expression was associated with a worse prognosis in meningioma (P<0.001), the same results were confirmed in the GEO database (P<0.001). Both EZH2 expression and H3K27me3 deletion (P=0.035) predicted a worse prognosis, but EZH2 has no correlation with H3K27me3 expression. EZH2 expression was closely associated with increased Ki67 index (P<0.001). In addition, EZH2 was associated with the immune microenvironment and positively correlated with PD-L1 expression (P<0.001). Conclusion: EZH2 is a new prognostic biomarker in meningioma. It correlates with PD-L1 expression and closely related to tumor immunosuppression. Our research can provide a reference for the potential targeted therapy and immunotherapy of meningioma in the future.